Persepsi Pelaku UMKM Kopi Bubuk Terhadap Sertifikasi Produk di Kabupaten Lampung Barat - Novia, Shanti; Ali, Suprihatin; Nugeraha, Prasetya (Jurnal Kompetitif Bisnis, 2022)
This study aims to determine the perception and interest of MSME actors in ground coffee towards product certification in West Lampung Regency. This type of research is descriptive research with a mixed methods approach. The research uses a quantitative approach and is then supported by qualitative research data. Data were collected through questionnaires and interviews. Data analysis was carried out by descriptive quantitative analysis and followed by descriptive qualitative analysis which included data collection, data reduction, data presentation and drawing conclusions or verification. Based on the results of research and data analysis in this study, it shows that product certification has a positive influence on the perception of ground coffee MSME actors in West Lampung Regency, thus making ground coffee MSME actors interested in certifying the products they market.